Notes on the subfamily Stenogastrinae (Hymenoptera: Vespidae) in the Philippine Islands, with description of nine new species - Selis, Marco (Zootaxa, 2018)
New additions to the subfamily Stenogastrinae in the Philippine Islands are provided. Nine new species are described: Liostenogaster maculiceps Selis, sp. nov., Parischnogaster albofasciata Selis, sp. nov., P. mindanaonis Selis, sp. nov., and P. simillima Selis, sp. nov., from Mindanao; P. curviclypeus Selis, sp. nov. from Mindoro; P. carpenteri Selis, sp. nov. from Mindanao and Mindoro; L. bimaculata Selis, sp. nov., from Mindanao and Samar; P. nigerrima Selis, sp. nov., and P. nigriterga Selis, sp. nov. from Luzon. The male of Eustenogaster fumipennis Saito and the female of Parischnogaster giglii Selis, are described for the first time. A key to the species of Liostenogaster van der Vecht occurring in the Philippine Islands and new distributional data are provided.